Severe functional retrograde amnesia: case report (Archives of Clinical Psychiatry, 2008)
BACKGROUND: A classic amnestic syndrome is characterized by a significant impairment of the anterograde memory, a variable and transitory retrograde amnesia with preserved non-declarative memory. However, case reports of patients with disproportionate compromise of the retrograde memory have been described in the recent literature. OBJECTIVES: To report a 26-year-old patient with a severe global retrograde amnesia with no evident triggering factor. METHODS: Psychiatric interview and neuropsychological evaluation. RESULTS: His memory loss compromised all domains of his life, although he could acquire and retain new information. He also exhibited prominent deficits in production and comprehension of common words as well as in recognition and use of objects. DISCUSSION: The final diagnostic formulation of the present case is difficult possibly indicating a continuum between psychogenic and organic retrograde amnesia.